High-efficiency generation of OAM-independent perfect vector vortices using multifocal phase-only silicon metalenses - Andrea Vogliardi; Gianluca Ruffato; Daniele Bonaldo; Simone Dal Zilio; Filippo Romanato (APL Photonics)
Perfect vortices have garnered significant attention due to their role as orbital angular momentum (OAM) beams with tunable ring-like intensity distributions. More recently, the non-separable combination of perfect vortices with opposite OAM and spin, known as perfect vector vortices, has extended their applicability in optical manipulation, high-resolution lithography, imaging, and telecommunications. The generation of perfect vector vortices with a size that remains constant regardless of the encoded topological charge typically requires both phase and amplitude modulation. In this study, we propose an efficient and innovative solution that leverages a multifocal approach encoded on phase-only silicon metalenses. A simultaneous control over dynamic and geometric phases was achieved through the careful design and fabrication of the individual meta-atoms comprising the metalens. This meta-atom engineering approach, modulating both phase components, enabled the generation and characterization of orbital angular momentum-independent perfect vector beams with an improved depth of focus. These devices represent a crucial step toward developing integrated optical architectures for information and communication technologies, with potential applications in both classical and quantum domains.